Is the Perceived Association between Chlamydia pneumoniae and Vascular Diseases Biased by Methodology? - Maraha, Boulos (American Society for Microbiology, 2004)
Inter- and intralaboratory inconsistencies in detection rates of Chlamydia pneumoniae in vascular specimens have been demonstrated. In this study, 66 vascular tissue specimens from 66 patients with vascular disease were tested by three PCR assays: a 16S PCR-based reverse line blot (RLB) assay, a single-step PCR, and a nested PCR. Also, we explored the impacts of different DNA polymerase enzymes on the results based on gel electrophoresis and hybridization. The PCR results by gel electrophoresis in the single-step PCR depended on which DNA polymerase was used. All samples were negative with AmpliTaq Gold DNA polymerase, and 54.5% (36 of 66) were positive with the conventional Taq DNA polymerase. All samples were negative after hybridization with a C. pneumoniae-specific probe. In the nested PCR, all specimens were negative by gel electrophoresis and after hybridization. The RLB assay failed to detect C. pneumoniae in any specimen; however, 20 specimens were Chlamydia sp. positive. The sequence analysis of six of these samples demonstrated Chlamydia-like organisms. RLB detected Chlamydia sp. DNA in water and in the elution buffer after passage of the Qiagen columns (11 of 40). This study identified factors that may influence the detection of C. pneumoniae DNA in vascular tissues and consequently bias the perception of a link between C. pneumoniae and vascular diseases. The following are strongly recommended: to use DNA polymerases that have to be activated, to decontaminate with dUTP-uracil-DNA glycosylase, to hybridize with specific probes, to include sufficient controls, and to use molecular grade water.